The Cambridge handbook of the imagination - Abraham, Anna (UK Cambridge University Press, 2020)
"O Imagination, you who steal men so From outer things that they would miss the sound Should in their ears a thousand trumpets blow, What moves you then, when all the senses drown? A light moves you, that finds its form in heaven, By itself, or by the will that guides it down.1 Let us reflect on the image presented in Figure 1.1. It shows a fragment, the remains of a statue from circa 1353-1336 BCE2. Although several key features are missing, we readily recognize a human face. If asked to imagine what the rest of the head might look like, we have little trouble undertaking this mental reconstruction. We can alter the features of summoned image to fit the description of man or woman, belonging to the peasantry or royalty. We can imagine a different headdress accompanying a queen of ancient Egypt compared to a goddess of ancient India. Indeed, we could go much further into the realm of hypotheticals by contemplating the potential musings of the creator of this work, the subject of this work, as well as the audience for this work"--
Includes index.
Keywords: Imagination